11th AIAA Aviation Technology, Integration, and Operations (ATIO) Conference 2011
DOI: 10.2514/6.2011-6802
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Controller Intervention Probabilities for Optimized Profile Descent Arrivals

Abstract: Simulations of arrival traffic at Dallas/Fort-Worth and Denver airportswere conducted to evaluate incorporating scheduling and separation constraints into advisories that define continuous descent approaches. The goal was to reduce the number of controller interventions required to ensure flights maintain minimum separation distances of 5 nmi horizontally and 1000 ft vertically. It was shown that simply incorporating arrival meter fix crossing-time constraints into the advisory generation could eliminate over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…As with previous studies into CDA (Errico and Di Vito, 2017;Murdoch et al, 2009), the systematic introduction of CCO means that: (1) ATC should avoid acting on CCO and (2) CCO will fly vertical profiles that are different to current (standard) departures (Mitchell et al, 2012;Torres et al, 2011). This second point means that new conflicts may arise while others will disappear (Lehouillier et al, 2017;Meyn et al, 2011;Mitchell et al, 2012;Vilardaga and Prats, 2014). The reason for this is that currently, departures are prevented from climbing to a specific Flight Level (FL) unless ATC issues a clearance.…”
Section: Literature Reviewmentioning
confidence: 72%
“…As with previous studies into CDA (Errico and Di Vito, 2017;Murdoch et al, 2009), the systematic introduction of CCO means that: (1) ATC should avoid acting on CCO and (2) CCO will fly vertical profiles that are different to current (standard) departures (Mitchell et al, 2012;Torres et al, 2011). This second point means that new conflicts may arise while others will disappear (Lehouillier et al, 2017;Meyn et al, 2011;Mitchell et al, 2012;Vilardaga and Prats, 2014). The reason for this is that currently, departures are prevented from climbing to a specific Flight Level (FL) unless ATC issues a clearance.…”
Section: Literature Reviewmentioning
confidence: 72%
“…Different authors confirmed that automation help ATC to deal with the introduction of new procedures based on optimised trajectories. 22,23 In this way, automation must address: (1) Compatibility with new operational concepts; (2) Capacity to favour the operation of optimised trajectories; and (3) Balance or improvement of safety levels. As previously stated, CCO trajectories may imply a modification of the current vertical profiles due to the avoidance of segregation requirements and, therefore, conflicts between CCOs and arrivals may arise.…”
Section: Introductionmentioning
confidence: 99%
“…2) The variability associated with climbing profiles can imply the appearance/disappearance of a high number of conflicts between CCO and arrival flows [62], [71], [72]. Thus, the impact of path uncertainties is crucial to assess the safety problem.…”
Section: Overview Of Eco-friendly and Cco Integrationmentioning
confidence: 99%